Neurotrauma Registries in Low- and Middle-Income Countries for Building Organized Neurotrauma Care: The LATINO Registry Experience; Comment on “Neurotrauma Surveillance in National Registries of Low- and Middle-Income Countries: A Scoping Review and Comparative Analysis of Data Dictionaries” - Andrés M. Rubiano; Angelica Clavijo (International Journal of Health Policy and Management, 2023)
Trauma registries play an important role in building capacity for trauma systems. Regularly, trauma registries exist in high-income countries (HICs) but not in low- and middle-income countries (LMICs). Neurotrauma includes common conditions, like traumatic brain injuries (TBIs) and spinal cord injuries. The development of organized neurotrauma care is crucial for improving the quality of care in less-resourced areas. The recent article published in International Journal of Health Policy and Management by Barthélemy et al entitled “Neurotrauma Surveillance in National Registries of Low- and Middle-Income Countries: A Scoping Review and Comparative Analysis of Data Dictionaries” adds an important body of literature to improve understanding of the importance of these types of efforts by promoting organized neurotrauma care systems in LMICs. Here, we provide a short commentary based on our experience with the Latin America and the Caribbean Neurotrauma Registry (LATINO-TBI) in the Latin America (LATAM) region.